Asymptomatic Achilles, patellar, and quadriceps tendinopathy: A longitudinal clinical and ultrasonographic study in elite fencers. Issue 3 (30th October 2011) - Giombini, A.; Dragoni, S.; Di Cesare, A.; Di Cesare, M.; Del Buono, A.; Maffulli, N.
<x xml:space="preserve">Abstract</x> Lower limb tendon changes detected at imaging are common among asymptomatic athletes. We aimed to prospectively assess the clinical status, tendon structure, and vascularity of lower limb tendons of elite fencers, and predict the risk of developing symptoms over time. Clinical examination, changes at ultrasonography (US), and Power Doppler (PD) flow of both the Achilles, patellar, and quadriceps tendon were assessed in 37 elite fencers in January 2007 and 3 years after. Two hundred and twenty‐two tendons were examined. At the last appointment, patellar tendons diagnosed as abnormal at baseline were more likely to develop symptoms than those normal at baseline (P < 0.05, Fisher's exact test), while US and PD abnormalities on Achilles and quadriceps tendons were no predictive for development of symptoms over years. A very low percentage of tendons diagnosed as normal at baseline (1.45%) showed US abnormalities at 3‐year follow‐up. In asymptomatic elite fencers, structural changes are relatively common at US and PD assessment of Achilles, quadriceps, and patellar tendons. It seems unlikely that additional PD investigations provide further information or change prognosis in patients with US diagnosis of tendinopathy.